From pandemic uncertainty to economic recovery: Does investor sentiment still matter for stock returns? - Sudaryanti, Dwiyani; Mohamad Bastomi (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2023)
The relationship between investor sentiment and market dynamics is a highly intriguing research topic for both academics and the financial industry. By using Spearman rank correlation analysis, this paper aims to explore investors’ decision-making behavior (rational and irrational) on stock returns during and after the COVID-19 outbreak. While irrational factors of the study were measured by the Google Search Volume Index and trading volume, rational factors were measured by profitability and size. The study used three different characteristics of subsectors manufacturing industry namely Food and Beverage, Pharmacy, and Cigarettes that are listed in the Indonesia Stock Market. To the best of our knowledge, our study is the first to examine and compare the level of rationality of investors in a wide range of industries and sectors during and after the COVID-19 pandemic. Our finding supports the notion that both sentiments have an effect on stock returns indicating that cognitions, emotions, and the noise of traders still have an impact on the market. While overall rational sentiment has a more significant correlation with stock returns during the economic recovery phase, there was a highly significant correlation between irrational factors and stock returns during pandemic uncertainty conditions. Moreover, investors tend to be irrational and overreact when making investment decisions in Cigarette sectors during the COVID-19 pandemic. In contrast, after the pandemic, the correlation of rational sentiment of investors toward the Pharmacy industry is still higher than others.